Novel strategy for reusing agricultural mulch film residual by iron modification for arsenic removal in gold-smelting wastewater - Zhang, Xiaozhuan; Zhao, Kejiang; Shi, Xibao; Tian, Zhenbang; Huang, Zuohua; Zhao, Liang (Frontiers in Chemistry, 2022)
In gold-smelting wastewater after the original treatment process of flocculation and precipitation using mainly lime, a mixture of As, Cu, Pb, Mn, Zn, Al, Ni, and Fe existed with an arsenic concentration of 813.07 mg/L and other ions’ concentration at ug/L levels. In this work, a new clean process of mainly adsorption with self-made adsorbent Fe-PE, which was synthesized by loading ferric lignin on agricultural mulch film residual, was investigated to purify and remove arsenic from gold-smelting wastewater. A batch of column experiments was investigated to explore the reaction behavior between wastewater and adsorbent Fe-PE. The results showed while operating the adsorption columns at a pilot scale for 68 days, the arsenic concentration in the effluent was below 0.5 mg/L, and there was no significant change in the concentration of co-existing metal ions, indicating that Fe-PE had a good selective adsorption performance for arsenic in wastewater. Furthermore, Fe-PE did not dissolve and release Fe ions in wastewater, and the whole process could not produce sludge. This work first suggested an efficient and potential application for the purification and removal of arsenic from gold-smelting wastewater with agricultural mulch film residual after chemical modification, which will provide a novel strategy for reusing the agricultural mulch film residual.